(Are) Institutions More Important Than Innovation?. Issue 2 (3rd April 2021) - Josifidis, Kosta; Supic, Novica
Abstract: The aim of this article is to shed more light on the effects of technological innovation on economic progress from the institutionalist perspective. Based on historical data on economic growth and technological changes in the United States, we question the assumption of mainstream economics that innovation, performed by profit-making enterprises, is a key source of productivity growth. The difference between the golden age and the period since suggests that economic progress is primarily determined by a successfully functioning institutional structure and progressive institutional changes.